CeO2 and Co3O4-CeO2 nanoparticles: effect of the synthesis method on the structure and catalytic properties in COPrOx and methanation reactions - Peiretti, Leonardo Federico (2016)
CeO2 and Co3O4–CeO2 nanoparticles were synthesized, thoroughly characterized, and evaluated in the COPrOx reaction. The CeO2 nanoparticles were synthesized by the diffusion-controlled precipitation method with ethylene glycol. A notably higher yield was obtained when H2O2 was used in the synthesis procedure. For comparison, two commercial samples of CeO2 nanoparticles (Nyacol®)—one calcined and the other sintered—were also studied. Catalytic results of bare CeO2 calcined at 500 °C showed a strong influence of the method of synthesis. Despite having similar BET area values, the CeO2 synthesized without H2O2 was the most active sample. Co3O4–CeO2 catalysts with three different Co/(Co + Ce) atomic ratios, 0.1, 0.3, and 0.5, were prepared by the wet impregnation of the CeO2 nanoparticles. TEM and STEM observations showed that impregnation produced mixed oxides composed of small CeO2 nanoparticles located both over the surface and inside the Co3O4 crystals. The mixed oxide catalysts prepared with a cobalt atomic ratio of 0.5 showed methane formation, which started at 200 °C due to the reaction between CO2 and H2. However, above 250 °C, the reaction between CO and H2 became important, thus contributing to CO elimination with a small H2 loss. As a result, CO could be totally eliminated in a wide temperature range, from 200 to 400 °C. The methanation reaction was favored by the reduction of the cobalt oxide, as suggested by the TPR experiments. This result is probably originated in Ce–Co interactions, related to the method of synthesis and the surface area of the mixed oxides obtained.